Implementasi IPA Terpadu Berbasis Komik di Kelas V SDN Paya Kalui Aceh Timur - Haris, Muhammad; Putra, Mulia; Akmaluddin, Akmaluddin; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2023)
Student involvement in science learning is very minus if the learning provided is not meaningful and less attractive to students. Conventional learning carried out by teachers does not provide confidence in the learning process has not had an impact on learning outcomes. This research aims to provide descriptive information about comic-based integrated science implemented in grade V of SD Negeri Paya Kalui East Aceh. This type of research is qualitative descriptive. Data were collected through observation and interviews. The stages of data analysis used are data reduction, data presentation, and conclusions. The results of data analysis showed that teachers made integrated science teaching media based on comics, namely by making picture books and having words and colors from the figure of someone who seemed to be talking, thinking, and doing something. The teacher demonstrates how cartoons speak in different tones and voices as if in a story there are many who play a role, but it is the teacher who speaks, exemplifying with different tones of voice and accents. Comic-based integrated science learning has a good impact and provides a unique and fun learning nuance for students so that learning looks meaningful and gives its own meaning to students.